Openbaring en integriteit: Een nieuwe context voor de systematische theologie - Erp, Stephan van (Tijdschrift voor theologie, 2007)
In the very first issue of this journal, Edward Schillebeeckx wrote about a new turn in dogmatic theology, concerned with anthropology and the historicity of faith and theology. Currently, Catholic theological faculties in the Netherlands are divided into departments of theology and of religious studies. In this article it is argued that this divide does not have to be the end of a hermeneutical theological tradition, although the author warns against the dangers of strong dichotomies in the description of differences between theology and religious studies. To prevent the application of these dichotomies in the division of tasks between these two disciplines, the history and methods of modern systematic theology should be considered carefully. First, the new Dutch landscape of the study of religion is described, after which the problems are explained that could emerge after a strong divide between religious studies and theology. Second, a description of the history of modern theology shows a heritage of theological debates on the interplay of church, academy and culture. Although systematic theology has more than once handed over several of its tasks to different theological and philosophical disciplines, it has also taken up methods and insights of other academic disciplines, like anthropology and the social sciences. The examples of Friedrich Schleiermacher, Karl Barth and David Tracy show this historical process and the debates that accompanied it. Furthermore, contemporary Dutch- Flemish literature on religion, faith and culture is evaluated from the viewpoint of the possible cohabitation of religious studies and theology. In the final section the two main tasks of systematic theology, reasoning about revelation and integrity, are contrasted with religious studies. The author refines the usual arguments against dogmatics, i.e. that hypotheses are impossible and that there is an interpenetration, undesirable in science, of the performative, the explicative and the epistemological. By combining Schillebeeckx’s idea of revelation with the idea of integrity of Rowan Williams, it is shown that the historicity of academic reflection makes performing the interests of an academic discipline unavoidable. The recent history of systematic theology has shown that religious studies and theology need each other to reflect on the performativity and perspectivity of their object of study and of their own fields.